The impact of the green energy transition at the local level. How just is the fast implementation of decarbonization policy in West Macedonia? - Boulogiorgou, Despoina; Kaldellis, John K. (Frontiers in Environmental Science, 2025)
The stability of Earth’s ecosystem is being seriously challenged by the pressing issues related to human-induced global warming and the climate crisis. However, the European political ambition of decarbonization (FIT for 55) has brought challenging circumstances for the European coal regions concerning job loss and regional economic decline. Until recently, coal activities offer direct employment to around 208,000 people across Europe, while local lignite-based activities put at risk almost 12,000 direct and indirect jobs in West Macedonia (W.M.) of Greece. For this purpose, the current study analyzes the impact of decarbonization policy in W.M. on the life quality of the local population and investigates the local factors’ effect on the successful implementation of this accelerated green energy transition strategy at community level. The applied methodology examines the decarbonisation and coal phase-out strategies at both the European Union and Greek level along with the presentation of the initial results of the coal phase-out policy’s implementation in the W.M. region. Accordingly, the attitude of the local community towards the decarbonization policy in the W.M. region is described. Finally, identification and emphasis on the knowledge transfer requirements for local communities to enable equitable societal engagement during the energy transition is highlighted.